Nitrogen Rate and Cutting Management for Fenugreek Green Leaf and Seed Production - Singh, Satybhan; Dhangrah, V. K.; Singh, Virendra; Thenua, O. V. S.; Pal, Krishan; Shukla, R. D. (International Journal of Bio-resource and Stress Management, 2018)
Fenugreek (Trigonella foenum-graecum L.) is an annual seed spice crop also used as a leafy vegetable, and reported to have medicinal properties. Farmers usually practice leaf cutting in fenugreek only when crop grown for vegetable purpose. There is need to standardize the nitrogen requirement when leaf cutting is practiced at different stages of growth since it may influence leaf and seed yields. Hence, present field Experiment was conducted to study the effect of Nitrogen rate and Cutting Management on Fenugreek leaf and seed production during 15th November, 2015 to 25th March, 2016. Treatments were comprised of three nitrogen levels of 20, 40 or 60 kg ha-1 and three levels of cutting i.e. no cutting, or cutting at 45 or 60 days after sowing (DAS). All treatment combinations were replicated 3 times in a factorial randomized complete block design. The observations were recorded on plant height, number of pods plant-1, number of seed pod-1, green leaf yield, seed yield and biological yield (sum of seed and straw yield). Harvest index was calculated by dividing economic yield to biological yield. The results revealed that increased green leaf and seed yields occurred when nitrogen level increased and cutting was delayed. The maximum harvest index (0.44) was when nitrogen was applied @ 60 kg ha-1 and plants were cut at 60 DAS. Thus, delaying cutting increases nitrogen requirement in fenugreek if supplied in proper amount, it results to increased yield.